Reducing Unnecessary CT Scanning in Head Trauma of Pediatric Patients: A Narrative Review - Alireza Baratloo; Mohammad-Taghi Talebian; Sahar Mirbaha; Shahram Bagheri-Hariri (Journal of Pediatrics Review, 2019)
Context: The current review article considered the latest published papers on reducing unnecessary head Computed Tomography (CT) scans in pediatric patients, to pave the way for further surveys. Evidence Acquisition: The papers were selected through Google Scholar and PubMed.  We searched “reducing unnecessary head CT scan in pediatric patients” with related keywords compatible with MeSH system in accordance with the search strategy. Original articles and systematic reviews published after 2010 were included. Other types of manuscripts such as a letter to editor, editorial reviews, case series, etc. were excluded. The title and abstract of the eligible articles were assessed in terms of relevance to our topic. The full text of final selected papers were studied by the investigators. Furthermore, a critical appraisal was performed in an expert panel to summarize it and make it applicable. Results: The extracted manuscripts have addressed this issue by various strategies. The findings could be categorized as follows: observation period, focused history taking, protocol and guideline development, implementation of validated clinical prediction rules, and blood-based decision making by assessing neuro-biomarker levels. Conclusions: Most of the reviewed articles were focused on clinical findings to discover  the minimum or low risk category of the pediatric patients with blunt head trauma. Other articles attempted on facilitating the use of available clinical prediction rules in this regard. Also, the measurement of serum biomarker levels has been considered; however, their widely application in practice is not well supported by evidence yet.